Challenges and Management Strategies of Elementary School Teachers in Addressing Artificial Intelligence (AI) Disruptions in Student Character Education - Ramlis Harman Susanto; Eliga Fitria; Surya Adri; Ayani Filko; Abhanda Amra (Journal Informatic, Education and Management (JIEM), 2026)
The disruption of Artificial Intelligence (AI) in the education sector presents a fundamental dualism: as an innovative instrument with transformative potential, but also as a significant challenge to the pillars of character education at the elementary school level. This article systematically examines these issues in the context of education in Indonesia. An in-depth analysis identifies three main dimensions of challenges faced by elementary school teachers: (1) ethical and moral challenges, including the erosion of academic integrity, threats to student data privacy, and algorithmic bias; (2) socio-emotional challenges, including the risk of empathy atrophy, social isolation due to reduced human interaction, and digital dependency; and (3) pedagogical challenges, highlighting the limitations of AI as a moral educator and a shift in learning focus that risks neglecting the affective domain. Facing these multidimensional challenges, the role of teachers undergoes a crucial transformation from information conveyors to digital character architects. Consequently, a strategic and comprehensive teacher management framework is needed. This article proposes a management strategy centered on four pillars: (1) adaptive continuing professional development (PKB) based on the Technological Pedagogical Content Knowledge (TPACK) framework; (2) transformative instructional leadership based on human-centric principles; (3) developing school curricula and policies that are responsive to AI ethics; and (4) strengthening the education ecosystem through synergistic collaboration between schools, parents, and the government. In conclusion, the success of integrating AI without sacrificing character education does not depend on technological sophistication, but rather on the readiness, competence, and resilience of teachers. Therefore, investing in human-centered teacher management is a definitive prerequisite for wisely harnessing the potential of AI while fortifying the foundation of the character of future generations.